RECOVERY, GROWTH AND CARCASS COMPOSITION FOLLOWING PERIODS OF RESTRICTED RATION AND FULL FEEDING IN INDIAN MAJOR CARP, ROHU (LABEO ROHJTA H.) - Prabhakar, Surya Kumar; Sardar, Parimal; Shah, Mukhtar Hussain (Journal of Indian Fisheries Association, 2006)
A 90-day experiment was conducted to determine the effect of restrictedration and full feeding on the recovery growth and carcass compositions of fingerlings (average weight- 20.74 ± 0.13 g) of rohu, Labeo rohita (H.). Rohu fingerlings procured from a local fish breeder were fed with commercial pelleted feed (27o/o crude protein) during the two-week acclimatization in the laboratory condition. Experimental pelleted diet (30% crude protein) was prepared and the control group (TcFR) was fed at 3o/o of body weight for the 90- day trial period. The experimental group T,,..R was fed for three days at 1